(untitled) (Window of Public Health Journal, 2026)
Based on 2023 data from the South Sulawesi Provincial Health Office, the highest prevalence of hypertension was in Makassar City, with 225,979 cases. The health center with the highest prevalence of hypertension in 2023 was the Kassi-Kassi Health Center, with 16,767 cases. This study aims to determine the effects of consuming JaSeKeh capsules (ginger, lemongrass, and cloves) and sunbathing on reducing blood pressure among hypertension patients in the Kassi Kassi Health Center work area. The research is quantitative. The research method used is a true experiment. The research design used is a pretest-posttest with a control group. The population in this study is the total number of people or individuals who are the source of the research. In this study, the population was all hypertension sufferers at the Kassi-Kassi Health Center, Rappocini District, Makassar City, South Sulawesi, and the sample comprised 30 respondents with pre-hypertension at the Kassi-Kassi Health Center, selected using the purposive sampling method. Data were analyzed using the normality test and the Wilcoxon test at the 95% significance level (P = 0.05). The results showed that consuming JaSeKeh capsules (ginger, lemongrass, cloves) had a significant effect on reducing systolic and diastolic blood pressure, with p-values of 0.001 (systolic) and 0.006 (diastolic). Meanwhile, the sunbathing intervention also showed a significant decrease, with a value of 0.005 (systolic) and 0.022 (diastolic). In conclusion, taking JaSeKeh capsules and sunbathing significantly reduced blood pressure in patients with hypertension. The researcher suggests that the Kassi-Kassi Health Center can utilize herbal ingredients such as ginger, lemongrass, and cloves as alternative therapies for hypertension.